Disenrollment Timeline Recommendation Briefing - Anna Benscoter:::Manger, Student Business Services:::; Stephanie Bracamontes::::::; Sunshine Garcia:::::: (2022)
The Executive Retention Steering Committee and colleagues from Student Business Services and Financial Aid & Scholarships were asked to provide recommendations to reduce the number of students that are eligible for disenrollment. As of August 15, 2022, Student Business Services implemented the following two recommendations.